2014
DOI: 10.1007/s00264-014-2514-8
|View full text |Cite
|
Sign up to set email alerts
|

“Sliding angulation osteotomy”: preliminary report of a novel technique of treatment for chronic radial head dislocation following missed Monteggia injuries

Abstract: Sliding angulation osteotomy is a technically simple procedure, which achieves lengthening and angulation of the ulna simultaneously in the sagittal plane and reduces the radial head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…For instance, follow-up time was set at 16.2 months in an early experience report [21] based on patients treated with locking plates for proximal humeral fractures, while mean PR can be an invaluable way to report early complications of new devices or adverse effects but they need to be read with caution when addressing surgical techniques or new implants results, as later-term papers can not be guaranteed. Moreover, [20] no complications reported Kay S et al [56] no complications reported Arciero R et al [1] 1 resubluxation Owens B et al [57] 6 redislocation (4 revisions) 9 subluxations (2 revisions) Goldberg et al [17] 1 adherences (revision) Manta JP et al [58] 5d i s l o c a t i o n s 3 resubluxations (revision) 12 subluxations 3 transient neuroapraxia 1 superficial wound infection Boulahia A et al [5] 1 glenoid loosening (revision) Guery J et al [59] 1 infection (revision) 1 dislocation (revision) 2 dislocations (reduction general anaest) 1 hematoma 3 glenoid unscrewed 1 phlebitis 1 glenoid loosening (revision) Burkhart S et al [7] no complications reported Denard PJ et al [60] 1 shoulder dislocation 2 revision after cuff repair Godenèche et al [16] 5 intraiperative fractures Raiss P et al [61] 13 implant loosening (revision) 1 deep infection (revision) 1 partial rupture of subscapularis (revision) 8 neurologic complications 4 hematoma 5 prosthetic instabilities considerations based on the findings presented in this paper may be extrapolated to recent papers in the different fields of orthopaedic surgery [68,69].…”
Section: Discussionmentioning
confidence: 79%
“…For instance, follow-up time was set at 16.2 months in an early experience report [21] based on patients treated with locking plates for proximal humeral fractures, while mean PR can be an invaluable way to report early complications of new devices or adverse effects but they need to be read with caution when addressing surgical techniques or new implants results, as later-term papers can not be guaranteed. Moreover, [20] no complications reported Kay S et al [56] no complications reported Arciero R et al [1] 1 resubluxation Owens B et al [57] 6 redislocation (4 revisions) 9 subluxations (2 revisions) Goldberg et al [17] 1 adherences (revision) Manta JP et al [58] 5d i s l o c a t i o n s 3 resubluxations (revision) 12 subluxations 3 transient neuroapraxia 1 superficial wound infection Boulahia A et al [5] 1 glenoid loosening (revision) Guery J et al [59] 1 infection (revision) 1 dislocation (revision) 2 dislocations (reduction general anaest) 1 hematoma 3 glenoid unscrewed 1 phlebitis 1 glenoid loosening (revision) Burkhart S et al [7] no complications reported Denard PJ et al [60] 1 shoulder dislocation 2 revision after cuff repair Godenèche et al [16] 5 intraiperative fractures Raiss P et al [61] 13 implant loosening (revision) 1 deep infection (revision) 1 partial rupture of subscapularis (revision) 8 neurologic complications 4 hematoma 5 prosthetic instabilities considerations based on the findings presented in this paper may be extrapolated to recent papers in the different fields of orthopaedic surgery [68,69].…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the lengths of corresponding dual plates differ from each other in currently available implant systems [17,18]. Biomechanical evidence is lacking thus far to support this recommendation regarding plate length and configuration.…”
Section: Discussionmentioning
confidence: 97%
“…Surgical instructions for double plate osteosynthesis recommend that the plates should vary in length to avoid peri-implant failure [16][17][18]. Therefore, the lengths of corresponding dual plates differ from each other in currently available implant systems [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is usually recommended for patients with pain or limited functionality with loss of elbow motion, in whom the concave morphology of the radial head is preserved 5. For this, there are various surgical treatment options, including open reduction of the radial head and ulnar osteotomy with or without annular ligament reconstruction (ALR),26789101112131415 closed reduction by ulnar correction using single-stage osteotomy,16171819 or gradual distraction lengthening using an external fixator 202122. Although many studies have reported various techniques, there is no established standard treatment protocol for missed Monteggia fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons have performed open reduction of the radial head as a first procedure before ulnar osteotomy or ALR to remove posttraumatic fibrosis and annular ligament remnants,7810152324 while others insist that indirect reduction of the radial head by ulnar osteotomy could achieve good results without open reduction 171819202122. Moreover, several papers have reported satisfactory results with open reduction alone in some patients with missed Monteggia fracture 1462526.…”
Section: Introductionmentioning
confidence: 99%